2009
DOI: 10.1002/jor.20811
|View full text |Cite
|
Sign up to set email alerts
|

Tendon structural and mechanical properties do not differ between genders in a healthy community‐dwelling elderly population

Abstract: Elderly women are reportedly at higher risk of falling than their male counterparts. Postural balance is highly associated with fall risk and is also correlated with tendon structural and mechanical properties. Gender differences in tendon properties could partly explain the discrepancy in fall risk. Thus the purpose of this study was to investigate the possible gender difference in tendon properties in the elderly. The properties of the patellar tendon of 55 elderly (men n ¼ 27, aged 72 AE 1 years, women n ¼ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 53 publications
6
28
2
1
Order By: Relevance
“…Although our subject population consisted of trained cyclists, we found variation in stiffness between subjects (Fig. 3), which is again consistent with previous literature (Burgess et al, 2009; Kubo et al, 2003; Duclay et al, 2009). Despite the relative homogeneity of our subject population the predictive relation between mass and tendon stiffness had poor predictive power, r 2 = 0.01, and this increased to only r 2 =0.19 when F max was used instead of mass for the regression: it is likely that there would be an even greater uncertainty in predicting tendon stiffness across different populations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although our subject population consisted of trained cyclists, we found variation in stiffness between subjects (Fig. 3), which is again consistent with previous literature (Burgess et al, 2009; Kubo et al, 2003; Duclay et al, 2009). Despite the relative homogeneity of our subject population the predictive relation between mass and tendon stiffness had poor predictive power, r 2 = 0.01, and this increased to only r 2 =0.19 when F max was used instead of mass for the regression: it is likely that there would be an even greater uncertainty in predicting tendon stiffness across different populations.…”
Section: Discussionsupporting
confidence: 91%
“…However, the accuracy of these simulations is sensitive to the values used for tendon stiffness and resting length (Gerus and Berton, 2012). Despite considerable variability in these tendon properties between individuals (Burgess et al, 2009; Kubo et al, 2003; Duclay et al, 2009), many studies use generic values for the tendon properties.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio was close to 0.5 for the GM and GL whereas the mean value was 0.23 for the SOL. This lower ratio for the soleus leads to tendon-aponeurosis characterization stiffer than the three others muscles but still less stiff than the generic condition currently used into EMG-driven model [7]. Taken together, these results suggest a clear difference in terms of mechanical properties of the SEE for the two conditions tested in the present study (i.e., generic vs. SS T-A).…”
Section: Discussionmentioning
confidence: 49%
“…Second, the generic definition is applied to models regardless of the nature of the task and the subject. Recent studies have shown a large variability in tendon mechanical properties depending on the sex [7], the type exercise [8], the age [9], and the loading rate (rate of force application to the tissue) [10], [11]. Finally, the generic definition is used to represent both the tendon and aponeurosis mechanical properties assuming their respective mechanical properties are equivalent.…”
Section: Introductionmentioning
confidence: 99%
“…Women, in particular, are more prone to falls and have a higher predisposition than men to fall-related injuries, namely, to osteoporotic fractures [3536]. Although several authors have cited sex differences in the mechanical properties of tendons to explain the discrepancies in the risks for falling [37], the reasons for a higher incidence of falls in women are not well known. One study reported that prevalence for fallers and the annual rates of falls were higher among women than men; however when controlled for each health or physical fitness variable, the Mantel-Haenszel test revealed no differences between the percentages of the men and the women who fall [38].…”
Section: Discussionmentioning
confidence: 99%